Acute lung injury after balloon pulmonary angioplasty results in a similar haemodynamic response and possible clinical advantage at follow‐up. (20th December 2022) - Rodgers, Matthew S.; Kirkby, Louise C.; Amaral‐Almeida, Liliana; Sheares, Karen; Toshner, Mark; Taboada, Dolores; Ng, Choo; Cannon, John E.; D'Errico, Luigia; Ruggiero, Alessandro; Screaton, Nicholas; Jenkins, David; et al.
Abstract: Acute lung injury (ALI) is a common but poorly defined and understood complication of balloon pulmonary angioplasty (BPA) for chronic thromboembolic pulmonary hypertension (CTEPH). Little data are available on the medium term clinical outcomes of BPA complicated by ALI. We analyzed per‐procedure data from 282 procedures in 109 patients and per‐patient data from 85 patients. Serial right heart catheterization at baseline, after each BPA and at 3‐month follow‐up measured pulmonary vascular resistance (PVR), mean pulmonary artery pressure (mPAP), and cardiac output (CO). ALI (ALI+) was identified by chest radiography alone (ALIr +) or in association with hypoxia clinically (ALIcr +). Procedural predictors of ALI and patient outcomes at 3‐months were compared no ALI (ALI−). ALI+ occurred in 17/282 (6.0%) procedures (ALIcr +: 2.5%, ALIr +: 3.5%). Prevailing haemodynamics (PVR: p  < 0.01; mPAP: p  < 0.05) at a procedural and patient level, as well as number of BPA sessions ( p  < 0.01), total number of vessels ( p  < 0.05), and occlusions ( p  < 0.05) treated at a patient level predicted ALI+. Those with ALI had greater percentage improvement in ΔCAMPHOR symptoms score (ALI+: −63.5 ± 35.7% ( p  < 0.05); ALIcr +: −84.4 ± 14.5% ( p  < 0.01); ALI−: −27.2 ± 74.2%) and ΔNT‐proBNP (ALIcr +: −78.4 ± 11.9% ( p  < 0.01); ALI−: −42.9 ± 36.0%) at follow‐up. There was no net significant difference in haemodynamic changes in ALI+ versus ALI− at follow‐up. ALI is predicted by haemodynamic severity, number of vessels treated, number of BPA sessions, and treating occlusive disease. ALI in this cohort was associated with a clinical advantage at follow‐up.